Phenotypic Variability and Genetic Diversity of the Pathogenic Fungus Macrophomina phaseolina from Several Hosts and Host Specialization in Strawberry - Viejobueno, Josefina; Santos, Berta de los; Camacho-Sánchez, Miguel; Aguado, Ana; Camacho, María; Salazar, Sergio Miguel (Springer, 2022)
Macrophomina phaseolina, is a pathogenic soil-borne fungus that affects more than 500 plant species, causing various types of disease to several crops, among which is the crown and root rot disease in strawberry. Its wide variability has been characterized reiteratively in the literature, but little is known about its virulence mechanisms. Morphological, physiological, genetic and phytopathogenic parameters were evaluated among 32 isolates of Macrophomina from different hosts occurring in Argentina and Spain. Colony characteristics, average size of microsclerotia, chlorate phenotype and mycelial growth at different temperatures (5º–40 °C), and pH (3.0–8.0) were recorded. The morphological and physiological traits were heterogeneous and did not show any association with the genetic structure nor with their pathogenicity. Most of the isolates (71.9%) exhibited chlorate-sensitive phenotype. The optimal growth temperature range was between 25 °C and 35 °C, and the optimal pH varied between 4.0 and 6.0. The genetic structure analyzed with four DNA markers (EF-1α, ITS, CAL and TUB) showed little diversity among isolates of M. phaseolina, with no clear association with the country of origin, but a significant association with the host. Based on their phylogenetic affinity, one isolate was reclassified as M. pseudophaseolina and another one as M. tecta. It is the first report of M. pseudophaseolina causing charcoal rot on beans, in Argentina, and the first report of M. tecta outside Australia. Pathogenicity tests on strawberry plants revealed marked host specialization, being the isolates obtained from strawberry more virulent than those from other hosts.